Synthesis and Antimicrobial Activity of 3-Substituted Phenyl-5-(5'-Substituted-2'-Phenylindol-3'-yl)-1,2-Diazoles and 3-Substituted Phenyl-5-(5'Substituted-2'-Phenylidol-3'-yl)-Isoxazoles - Patil, Renukadevi; Biradar, J.S. (Asian Journal of Chemistry, 2010)
5-Substituted-2-phenylindol-3-carboxaldehydes (Ia-c) were condensed with substituted acetophenones (IIa-h) in ethylene glycol and catalytic amount of piperidine afforded 5-substituted-2-phenylindol-3-chalcones (IIIa-x). These compounds, on reaction with hydrazine hydrate in absolute alcohol and hydroxylamine hydrochloride in alcoholic sodium hydroxide yielded 3-substituted phenyl-5-(5´-substituted-2´-phenylindol-3´ -yl)-1,2- diazoles (IVa-x) and 3-substituted phenyl-5-(5´-substituted-2-phenylindol- 3´-yl) isoxazoles (Va-x), respectively. The newly sysnthesised compounds were characterised by their analytical and spectral data. All these compounds were screened for antimicrobial activity against S. aureus, E. coli, A. niger and C. albicans.